Exploring of Arabic Text Book for MA KMA 183 in 2019 Based on Mackey’s Theory and ACTFL Standards - Husnatul Hamidiyyah Siregar; Moh. Ainin; Muassomah; Dadang Firdaus; Rendi Pramadi (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2022)
This study aims to explore Arabic textbooks by looking at four elements, namely selection (material selection), gradation (ordering), presentation, and repetition in Arabic textbooks for Class XI MA Curriculum KMA 183 in 2019 according to the theory of William Francis Mackey and explore Arabic language skills on textbook content according to the ACTFL standard perspective. This study uses qualitative research methods with descriptive analysis techniques and content analysis sourced from documentation data in Arabic textbooks for Class XI MA Curriculum KMA 183 in 2019, related books, articles, and journals. The results of the study show that the Arabic language textbooks for class XI KMA 183 in 2019 as a whole have met the criteria of Mackey's theory in four aspects. In the element of selection, the book has met three criteria for validity in the content and components of the book, including the parts of learning objectives, the level of students' abilities, and the type of language used. Furthermore, the gradation aspect of each subject matter in chapters 1 to 6 consists of listening, speaking, reading, writing, and tarākib skills, each related to and supporting one another with deductive and inductive sequencing methods. In the presentation aspect, three procedures are used in the book: differentiation, intensive and pictorial procedures. Each stage of the book presentation uses two languages, Arabic and Indonesian, utilizing the help of image object media to make it easier for students to understand the material. In the aspect of repetition, several tadribāt and materials are presented repeatedly with different themes in each chapter in the four Arabic language skills. The analysis of Arabic skills on Arabic books for class XI KMA 183 in 2019 according to the ACTFL standard perspective is divided into three levels: intermediate, low, mid, and high. Each group is classified according to the content of the material, indicators, and evaluation of learning in each of the four mahārah in six chapters, namely mahārah istimā', kalām, qirā’ah, and kitābah. Keywords: ACTFL, Arabic Language, Text Book, Mackey's Theory Abstrak Penelitian ini bertujuan untuk untuk mengeksplorasi buku ajar bahasa Arab dengan cara melihat empat unsur yaitu seleksi (pemilihan materi), gradasi (pengurutan), presentasi, repetisi dalam buku ajar bahasa Arab Kelas XI MA Kurikulum KMA 183 tahun 2019 menurut teori William Francis Mackey dan mengeksplorasi keterampilan bahasa Arab pada isi buku ajar menurut perspektif standar ACTFL. Penelitian ini menggunakan metode penelitian kualitatif dengan teknik analisis deskriptif dan analisis konten yang bersumber dari data dokumentasi pada buku ajar bahasa Arab Kelas XI MA Kurikulum KMA 183 tahun 2019, buku, artikel dan jurnal yang terkait. Hasil dari penelitian menunjukkan bahwa buku ajar bahasa Arab kelas XI KMA 183 tahun 2019 secara keseluruhan telah telah memenuhi kriteria teori Mackey dalam empat aspek. Pada aspek seleksi, buku telah memenuhi tiga kriteria keabsahan pada isi dan komponenen buku diantaranya pada komponen tujuan pembelajaran, tingkat kemampuan siswa, tipe bahasa yang digunakan. Selanjutnya pada aspek gradasi setiap materi pelajaran pada bab 1 sampai 6 terdiri dari keterampilan menyimak, berbicara, membaca, menulis dan tarākib yang masing-masing setiap keterampilan berkaitan dan mendukung satu sama lain dengan matode pengurutan deduktif dan induktif.Pada aspek presentasi ada tiga prosedur yang digunakan pada buku yaitu prosedur differensiasi, ontensive dan piktorial. Setiap tahapan presentasi buku menggunakan dua bahasa yaitu bahasa Arab dan bahasa Indonesia dengan menggunakan bantuan media obyek gambar untuk memudahkan siswa dalam memahami materi. Pada aspek repetisi, ada beberapa tadribāt dan materi yang disajikan secara berulang dengan tema yang berbeda pada setiap babnya dalam empat keterampilan bahasa Arab. Adapun analisis keterampilan berbahasa Arab terhadap buku bahasa Arab kelas XI KMA 183 tahun 2019 menurut perspektif standar ACTFL terbagi menjadi tiga tingkatan yaitu intermediate low, mid dan high. Setiap tingkatan diklasifikasikan sesuai muatan materi, indikator, dan evaluasi pembelajaran pada setiap empat mahārah dalam enam bab, yaitu mahārah istimā’, kalām, qirā’ah, and kitābah. Kata Kunci: ACTFL, Bahasa Arab, Buku Teks, Teori Mackey